Successful Intensive Care Management of a Newly Diagnosed HIV Patient Presented with Acute Respiratory Distress Syndrome Secondary to PJP: A Case Report and Literature Review - Muhamad Rafiqi Hehsan (Universiti Sultan Zainal Abidin (UniSZA), 2024)
Indexed by MyCite